2001
DOI: 10.1021/nl005521z
|View full text |Cite
|
Sign up to set email alerts
|

Fast Electron Transfer Kinetics on Multiwalled Carbon Nanotube Microbundle Electrodes

Abstract: The rate of electron transfer at carbon electrodes depends on various factors such as the structure and morphology of the carbon material used in the electrodes. With the advent of new carbon structures, such as fullerenes and carbon nanotubes, well-defined carbon surfaces have become available to probe electron-transfer kinetics on these surfaces. We show here that micron-size electrodes made of multiwalled carbon nanotubes show Nernstien behavior and fast electron-transfer kinetics for electrochemical reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
306
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 506 publications
(322 citation statements)
references
References 14 publications
13
306
0
3
Order By: Relevance
“…The average k 0 values were found to be (6.2 ± 1.4) × 10 -3 and (10.2 ± 5.1) × 10 -3 cms -1 for the bare and SWCNT-modified Au electrodes respectively. We note that our SWCNT modified gold electrodes are not as catalytically active as those reported recently by Nugent and co-workers [15]. The latter reported similar experiments conducted on MWCNT modified platinum electrode surfaces and reported that the ET rate constant for ferrocyanide oxidation is k 0 ≈ 0.5 cm s -1 .…”
Section: Electrochemical Characterization and Electron Transfer Dynamsupporting
confidence: 74%
“…The average k 0 values were found to be (6.2 ± 1.4) × 10 -3 and (10.2 ± 5.1) × 10 -3 cms -1 for the bare and SWCNT-modified Au electrodes respectively. We note that our SWCNT modified gold electrodes are not as catalytically active as those reported recently by Nugent and co-workers [15]. The latter reported similar experiments conducted on MWCNT modified platinum electrode surfaces and reported that the ET rate constant for ferrocyanide oxidation is k 0 ≈ 0.5 cm s -1 .…”
Section: Electrochemical Characterization and Electron Transfer Dynamsupporting
confidence: 74%
“…2). A fully reversible redox behaviour of hexaamineruthenium(III) was observed, with the cathodic and anodic peaks situated at ∼−0.220 and −0.160 mV, respectively, suggesting ideal reversibility at the electrode, as was also observed with Fe(CN) 6 3−/4− at MWCNT-modified electrodes [44]. A linear dependence of peak current on square root of scan rate was found with a slope of 142 A V −1/2 s 1/2 .…”
Section: Carbon Film Electrode Supportsupporting
confidence: 57%
“…CNTs behave electrically as a metal or semiconductor. The electronic properties suggest that CNTs have the capability to promote charge-transfer reactions when used as an electrode [15]. The modification of traditional electrode materials with carbon nanotubes for use in analytical sensing is well evidenced and characterized by lower detection limits, increased sensitivities, reduced overpotentials and increased resistance to surface fouling.…”
Section: Scheme 1 Structure Of Mitoxantronementioning
confidence: 99%